The northern California current on fire: consequences of a widespread and persistent anomalous pyrosome bloom - Richard D. Brodeur; Dylan G.E. Gomes; Douglas L. Draper; Elizabeth A. Daly; Samantha M. Zeman; Moira Galbraith; R. Ian Perry; James J. Ruzicka; Roxanne R. Robertson (Progress in Oceanography, 2026)

Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Open Questions on Ion–Neutral Collisions and Coupling in the Lower Thermosphere–Ionosphere: Electrodynamics, Energetics and Dynamics - Theodoros E. Sarris; Stelios Tourgaidis; Dimitrios Baloukidis; Maxime Grandin; Astrid Maute; Robert F. Pfaff; Jeffrey Thayer; James Clemmons; Karl Laundal; Hanli Liu; Panagiotis Pirnaris; Noora Partamies; et al. (Surveys in Geophysics, 2026)
The Lower Thermosphere–Ionosphere (LTI) is the interface region between the Earth’s atmosphere and space. It is modulated by the energy and momentum deposition from the magnetosphere above and by the impacting waves from the lower atmosphere. The LTI region is defined by the co-existence and interaction of neutral and ionized species within the region’s electric and magnetic fields. This interplay results in unique and complex interactions between neutrals and plasmas, that are not fully understood and quantified to this date. In this paper we present an overview of some of the most important open questions related to ion/neutral coupling and the resulting collisional electrodynamics, collisional energetics and collisional dynamics processes. We outline the key reasons for addressing these questions, and highlight methodologies that can lead to their closure in the upcoming years.

Social and Ecological Context Shape Biological Invasions in Complex Landscapes - George L. W. Perry; James M. R. Brock; Cameron B. Guy; Casey Hamilton; Finnbar Lee; Dion L. Pou; Elizabeth Williams; Erica A. H. Smithwick (Current Landscape Ecology Reports, 2025)

Comment on “Tianeptine Exposures Reported to United States Poison Centers, 2015–2023” - James B. Leonard; Perry E. Rosen; Christopher J. Counts (Journal of Medical Toxicology, 2025)

Climate media amidst technopolitical change: challenges, transformations, and new directions for research - Rachel Wetts; Hanna E. Morris; Maxwell Boykoff; Brenda McNally; James Painter; Mary Sanford; Emily P. Diamond; Marc Esteve-del-Valle; Loredana Loy; Kelly E. Perry; Urooj S. Raja; Robin Tschötschel (Climatic Change, 2025)
In this essay, we seek to provide a meta-level view of research on mediated climate change communication, taking stock of its achievements, historical and contemporary challenges, and future directions. While existing climate media scholarship has generated important insights to guide research and practice, recent empirical developments and technopolitical transformations challenge the traditional structure of climate media research. Historically, this research developed a tripartite structure where scholars have tended to focus on one of three distinct phases of the mediated communication process: (1) the production of narratives, frames, images, and other forms of communication about climate change; (2) the content and dissemination of these communication artifacts by and across media industries and institutions; and (3) these artifacts’ reception by and effects on policymakers, partisans, and publics. However, recent developments in communication technologies, media ecosystems, and the broader political landscape—including the increasing importance of social media and AI, new forms of climate obstruction, and rising antidemocratic forces across borders—have made these traditional lines of demarcation increasingly unworkable. While the lines of demarcation between production, dissemination, and reception are increasingly blurred in important new empirical phenomena, each has remained central in many scholarly works and the development of research questions. This persistence of the tripartite model, we argue, has caused climate media research to be slow to reflect the shifting dynamics of mediated climate communication today. After describing and analyzing the structural challenges that make doing more comprehensive climate media research so challenging, we conclude with proposals for new directions for scholarship that can help future research more fully contend with recent technopolitical transformations and move towards actionable research that is capable of grappling with and motivating robust responses to the complexities of climate change amid mounting authoritarian threats.

Documenting, quantifying, and modeling a large glide avalanche in Glacier National Park, Montana, USA - James Dillon; Erich Peitzsch; Zachary Miller; Perry Bartelt; Kevin Hammonds (Cold Regions Science and Technology, 2025)

Assessing greenspace and cardiovascular health through deep-learning analysis of street-view imagery in a cohort of US children - Li Yi; Sheryl Rifas-Shiman; Marcia Pescador Jimenez; Pi-I Debby Lin; Esra Suel; Perry Hystad; Andrew Larkin; Steve Hankey; Wenwen Zhang; Jochem Klompmaker; Emily Oken; Marie-France Hivert; et al. (Environmental Research, 2025)

Evaluating the effects of two newly emerging plant pathogens on northern Aotearoa-New Zealand forests using an individual-based model - Craig E. Simpkins; Peter J. Bellingham; Kiri Reihana; James M.R. Brock; George L.W. Perry (Ecological Modelling, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The mouse metabolic phenotyping center (MMPC) live consortium: an NIH resource for in vivo characterization of mouse models of diabetes and obesity - Maren Laughlin; Richard McIndoe; Sean H. Adams; Renee Araiza; Julio E. Ayala; Lucy Kennedy; Louise Lanoue; Louise Lantier; James Macy; Eann Malabanan; Owen P. McGuinness; Rachel Perry; et al. (Mammalian Genome, 2024)
The Mouse Metabolic Phenotyping Center (MMPC) Live Program was established in 2023 by the National Institute for Diabetes, Digestive and Kidney Diseases (NIDDK) at the National Institutes of Health (NIH) to advance biomedical research by providing the scientific community with standardized, high quality phenotyping services for mouse models of diabetes and obesity. Emerging as the next iteration of the MMPC Program which served the biomedical research community for 20 years (2001–2021), MMPC Live is designed as an outwardly-facing consortium of service cores that collaborate to provide reduced-cost consultation and metabolic, physiologic, and behavioral phenotyping tests on live mice for U.S. biomedical researchers. Four MMPC Live Centers located at universities around the country perform complex and often unique procedures in vivo on a fee for service basis, typically on mice shipped from the client or directly from a repository or vendor. Current areas of expertise include energy balance and body composition, insulin action and secretion, whole body carbohydrate and lipid metabolism, cardiovascular and renal function, food intake and behavior, microbiome and xenometabolism, and metabolic pathway kinetics. Additionally, an opportunity arose to reduce barriers to access and expand the diversity of the biomedical research workforce by establishing the VIBRANT Program. Directed at researchers historically underrepresented in the biomedical sciences, VIBRANT-eligible investigators have access to testing services, travel and career development awards, expert advice and experimental design consultation, and short internships to learn test technologies. Data derived from experiments run by the Centers belongs to the researchers submitting mice for testing which can be made publicly available and accessible from the MMPC Live database following publication. In addition to services, MMPC Live staff provide expertise and advice to researchers, develop and refine test protocols, engage in outreach activities, publish scientific and technical papers, and conduct educational workshops and training sessions to aid researchers in unraveling the heterogeneity of diabetes and obesity.

Quantification of CD3, FoxP3, and granzyme B immunostaining in canine renal cell carcinoma - Ashleigh Cournoyer; Hayley Amerman; Charles-Antoine Assenmacher; Amy Durham; James A. Perry; Allison Gedney; Nicholas Keuler; Matthew J. Atherton; Jennifer A. Lenz (Veterinary Immunology and Immunopathology, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Sensorimotor Cough Dysfunction in Cerebellar Ataxias - Emilie R. Lowell; James C. Borders; Sarah E. Perry; Avery E. Dakin; Jordanna S. Sevitz; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2023)

Coral adaptive capacity insufficient to halt global transition of coral reefs into net erosion under climate change - Christopher Edward Cornwall; Steeve Comeau; Simon D. Donner; Chris Perry; John Dunne; Ruben van Hooidonk; James S. Ryan; Cheryl A. Logan (Global Change Biology, 2023)
Projecting the effects of climate change on net reef calcium carbonate production is critical to understanding the future impacts on ecosystem function, but prior estimates have not included corals' natural adaptive capacity to such change. Here we estimate how the ability of symbionts to evolve tolerance to heat stress, or for coral hosts to shuffle to favourable symbionts, and their combination, may influence responses to the combined impacts of ocean warming and acidification under three representative concentration pathway (RCP) emissions scenarios (RCP2.6, RCP4.5 and RCP8.5). We show that symbiont evolution and shuffling, both individually and when combined, favours persistent positive net reef calcium carbonate production. However, our projections of future net calcium carbonate production (NCCP) under climate change vary both spatially and by RCP. For example, 19%–35% of modelled coral reefs are still projected to have net positive NCCP by 2050 if symbionts can evolve increased thermal tolerance, depending on the RCP. Without symbiont adaptive capacity, the number of coral reefs with positive NCCP drops to 9%–13% by 2050. Accounting for both symbiont evolution and shuffling, we project median positive NCPP of coral reefs will still occur under low greenhouse emissions (RCP2.6) in the Indian Ocean, and even under moderate emissions (RCP4.5) in the Pacific Ocean. However, adaptive capacity will be insufficient to halt the transition of coral reefs globally into erosion by 2050 under severe emissions scenarios (RCP8.5).

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The effect of exercise on left ventricular global longitudinal strain - James Murray; Hunter Bennett; Eva Bezak; Rebecca Perry; Terry Boyle (European Journal of Applied Physiology, 2022)
Exercise improves measures of cardiovascular (CV) health and function. But as traditional measures improve gradually, it can be difficult to identify the effectiveness of an exercise intervention in the short-term. Left ventricular global longitudinal strain (LVGLS) is a highly sensitive CV imaging measure that detects signs of myocardial dysfunction prior to more traditional measures, with reductions in LVGLS a strong prognostic indicator of future CV dysfunction and mortality. Due to its sensitivity, LVGLS may offer useful method of tracking the effectiveness of an exercise intervention on CV function in the short-term, providing practitioners useful information to improve patient care in exercise settings. However, the effect of exercise on LVGLS is unclear. This systematic review and meta-analysis aimed to determine the effect exercise has on LVGLS across a range of populations. Included studies assessed LVGLS pre–post an exercise intervention (minimum 2 weeks) in adults 18 years and over, and were published in English from 2000 onwards. Study-level random-effects meta-analyses were performed using Stata (v16.1) to calculate summary standardized mean differences (SMD) and 95% confidence intervals (CI). 39 studies met selection criteria, with 35 included in meta-analyses (1765 participants). In primary analyses, a significant improvement in LVGLS was observed in populations with CV disease (SMD = 0.59; 95% CI 0.16–1.02; p = 0.01), however, no significant effect of exercise was observed in CV risk factor and healthy populations. In populations with CV disease, LVGLS could be used as an early biomarker to determine the effectiveness of an exercise regime before changes in other clinical measures are observed.

The Effect of Marsh Age on Ecosystem Function in a Rapidly Transgressing Marsh - Amy K. Langston; Daniel J. Coleman; Nathalie W. Jung; Justin L. Shawler; Alexander J. Smith; Bethany L. Williams; Serina S. Wittyngham; Randolph M. Chambers; James E. Perry; Matthew L. Kirwan (Ecosystems, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Side-Population Trophoblasts Exhibit the Differentiation Potential of a Trophoblast Stem Cell Population, Persist to Term, and are Reduced in Fetal Growth Restriction - Teena KJB Gamage; Jasper J Perry; Vicky Fan; Katie Groom; Lawrence W Chamley; Joanna L James (Stem Cell Reviews and Reports, 2020)

Physician perceptions of a multidisciplinary endocarditis team - Sami El-Dalati; Irina Khurana; Nathaniel Soper; Daniel Cronin; Michael Shea; Richard L. Weinberg; James Riddell; Laraine Washer; Emily Shuman; James Burke; Sadhana Murali; D. Alexander Perry; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Determining the underlying structure of insular isolation measures - Zachary T. Carter; George L. W. Perry; James C. Russell (Journal of Biogeography, 2020)
Aim Island isolation is measured in many ways. We seek to determine what the underlying latent factors characterizing these measures are, in order to understand how they mechanistically drive island biogeographical patterns and in order to recommend the most parsimonious measures. We then test the discriminatory power of the identified components against hypotheses generated from the biogeographical patterns of invasive rats. Location The 890 offshore islands (≥1 hectare area) of the New Zealand archipelago (latitude: 34.1–47.3°S, longitude: 166.2–178.4°E). Taxon Mammals. Methods We identified 16 measures that have been frequently used to characterize isolation in the past, including Euclidean‐based distance metrics, landscape connectivity metrics derived from least‐cost and circuit theory modelling, landscape buffers, stepping stones and insular area. We used principal components analysis (PCA) to synthesize the underlying structure of insular isolation with respect to terrestrial mammal dispersal. Finally, we tested the discriminatory power of retained principal components (PCs) using permutational multivariate analyses of variance (PERMANOVA). Tests include comparison of historical rat distributions, islands targeted for rat eradication and islands reinvaded by rats. Results The underlying structure of island isolation as characterized in the 16 metrics was described by three independent PCA components. Variable clustering suggests that PC1 captured distance from the mainland source to the focal island (PC1 Distance), PC2 described stepping stones available along the dispersal pathway (PC2 Stepping Stones) and PC3 described the focal island's position in the landscape (PC3 Insular Network). Each discriminatory test affirmed its respective biogeographical pattern hypothesis. Main conclusions The three underlying components we identify form the basis of a robust description of insular isolation that is of broad importance to understanding island biogeography dynamics. Moreover, these components can be applied across taxa without extensive structural or functional assumptions because the highest loading variables are not biologically informed.

Early-earth nonprotein amino acid metabolites in modern cyanobacterial microbialites - Stephanie L. Bishop; Fiona J. M. Tymm; Karen Perry; Jeff K. Kerkovius; Frederic Menard; Allyson Brady; Greg Slater; Darlene S. S. Lim; James S. Metcalf; Sandra A. Banack; Paul A. Cox; Susan J. Murch (Environmental Chemistry Letters, 2020)

Cerebrovascular haemodynamics during isometric resistance exercise with and without the Valsalva manoeuvre - Blake G. Perry; Tom De Hamel; Kate N. Thomas; Luke C. Wilson; Travis D. Gibbons; James D. Cotter (European Journal of Applied Physiology, 2020)

Enhancing gardens as habitats for soil-surface-active invertebrates: should we plant native or exotic species? - Andrew Salisbury; Sarah Al-Beidh; James Armitage; Stephanie Bird; Helen Bostock; Anna Platoni; Mark Tatchell; Ken Thompson; Joe Perry (Biodiversity and Conservation, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Advocating for Science: Amici Curiae Brief of Wetland and Water Scientists in Support of the Clean Water Rule - Royal C. Gardner; Erin Okuno; Steph Tai; M. Siobhan Fennessy; Carol A. Johnston; Marinus L. Otte; Margaret Palmer; James E. Perry; Charles Simenstad; Benjamin R. Tanner; Dan Tufford; R. Eugene Turner; et al. (Wetlands, 2019)

Rise Up, Get Tested, and Live: an Arts-Based Colorectal Cancer Educational Program in a Faith-Based Setting - Daniela B. Friedman; Swann Arp Adams; Heather M. Brandt; Sue P. Heiney; James R. Hébert; John R. Ureda; Jessica S. Seel; Courtney S. Schrock; Wilhelmenia Mathias; Vivian Clark-Armstead; Reverend Vernette Dees; Reverend Perry Oliver (Journal of Cancer Education, 2019)

Carbon dioxide enrichment alters predator avoidance and sex determination but only sex is mediated by GABAA receptors - Jean-Claude Abboud; Edgar A. Bartolome; Mayra Blanco; Annalise C. Kress; Ian Y. Ellis; Perry K. Yazzolino; Kamrin I. Sorensen; James R. Winslow; David A. Cleary; Hugh Lefcort (Hydrobiologia, 2019)

A test of top-down control on plant production and nutrient quality in low-salinity tidal marshes - Lori A. Sutter; Randy M. Chambers; Madeline Karp; James E. Perry (Aquatic Sciences, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Enhancing gardens as habitats for plant-associated invertebrates: should we plant native or exotic species? - Andrew Salisbury; Sarah Al-Beidh; James Armitage; Stephanie Bird; Helen Bostock; Anna Platoni; Mark Tatchell; Ken Thompson; Joe Perry (Biodiversity and Conservation, 2017)

Adult-onset opsoclonus-myoclonus syndrome due to West Nile Virus treated with intravenous immunoglobulin - Julien Hébert; David Armstrong; Nick Daneman; Jennifer Deborah Jain; James Perry (Journal of NeuroVirology, 2017)

Phenotypic variation and identification of quantitative trait loci for ozone tolerance in a Fiskeby III × Mandarin (Ottawa) soybean population - Amy L. Burton; Kent O. Burkey; Thomas E. Carter; James Orf; Perry B. Cregan (Theoretical and Applied Genetics, 2016)

Climate and edaphic controllers influence rhizosphere community assembly for a wild annual grass - Erin E. Nuccio; James Anderson‐Furgeson; Katerina Y. Estera; Jennifer Pett‐Ridge; Perry de Valpine; Eoin L. Brodie; Mary K. Firestone (Ecology, 2016)
The interface between roots and soil, known as the rhizosphere, is a dynamic habitat in the soil ecosystem. Unraveling the factors that control rhizosphere community assembly is a key starting point for understanding the diversity of plant‐microbial interactions that occur in soil. The goals of this study were to determine how environmental factors shape rhizosphere microbial communities, such as local soil characteristics and the regional climate, and to determine the relative influence of the rhizosphere on microbial community assembly compared to the pressures imposed by the local and regional environment. We identified the bacteria present in the soil immediately adjacent to the roots of wild oat ( Avena spp .) in three California grasslands using deep Illumina 16S sequencing. Rhizosphere communities were more similar to each other than to the surrounding soil communities from which they were derived, despite the fact that the grasslands studied were separated by hundreds of kilometers. The rhizosphere was the dominant factor structuring bacterial community composition (38% variance explained), and was comparable in magnitude to the combined local and regional effects (22% and 21%, respectively). Rhizosphere communities were most influenced by factors related to the regional climate (soil moisture and temperature), while background soil communities were more influenced by soil characteristics ( pH , CEC , exchangeable cations, clay content). The Avena core microbiome was strongly phylogenetically clustered according to the metrics NRI and NTI , which indicates that selective processes likely shaped these communities. Furthermore, 17% of these taxa were not detectable in the background soil, even with a robust sequencing depth of approximately 70,000 sequences per sample. These results support the hypothesis that roots select less abundant or possibly rare populations in the soil microbial community, which appear to be lineages of bacteria that have made a physiological tradeoff for rhizosphere competence at the expense of their competitiveness in non‐rhizosphere soil.

Heart rate analysis by sparse representation for acute pain detection - Shai Tejman-Yarden; Ofer Levi; Alex Beizerov; Yisrael Parmet; Tu Nguyen; Michael Saunders; Zvia Rudich; James C. Perry; Dewleen G. Baker; Tobias Moeller-Bertram (Medical & Biological Engineering & Computing, 2016)

Response of temperate lakes to drought: a paleolimnological perspective on the landscape position concept using diatom-based reconstructions - Courtney R. Wigdahl-Perry; Jasmine E. Saros; Jennifer Schmitz; Randy Calcote; James Rusak; Dennis Anderson; Sara Hotchkiss (Journal of Paleolimnology, 2016)

Computational Modeling of Pathophysiologic Responses to Exercise in Fontan Patients - Ethan Kung; James C. Perry; Christopher Davis; Francesco Migliavacca; Giancarlo Pennati; Alessandro Giardini; Tain-Yen Hsia; Alison Marsden (Annals of Biomedical Engineering, 2015)

Erratum to: Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Hydrologic and Water Quality Model Development Using Simulink - James Bowen; David Perry; Colin Bell (Journal of Marine Science and Engineering, 2014)
A stormwater runoff model based on the Soil Conservation Service (SCS) method and a finite-volume based water quality model have been developed to investigate the use of Simulink for use in teaching and research. Simulink, a MATLAB extension, is a graphically based model development environment for system modeling and simulation. Widely used for mechanical and electrical systems, Simulink has had less use for modeling of hydrologic systems. The watershed model is being considered for use in teaching graduate-level courses in hydrology and/or stormwater modeling. Simulink’s block (data process) and arrow (data transfer) object model, the copy and paste user interface, the large number of existing blocks, and the absence of computer code allows students to become model developers almost immediately. The visual depiction of systems, their component subsystems, and the flow of data through the systems are ideal attributes for hands-on teaching of hydrologic and mass balance processes to today’s computer-savvy visual learners. Model development with Simulink for research purposes is also investigated. A finite volume, multi-layer pond model using the water quality kinetics present in CE-QUAL-W2 has been developed using Simulink. The model is one of the first uses of Simulink for modeling eutrophication dynamics in stratified natural systems. The model structure and a test case are presented. One use of the model for teaching a graduate-level water quality modeling class is also described.

Tidal Freshwater Marsh Plant Responses to Low Level Salinity Increases - Lori A. Sutter; James E. Perry; Randy M. Chambers (Wetlands, 2014)

Acute anxiety increases the magnitude of the cold shock response before and after habituation - Martin James Barwood; Jo Corbett; Richard Green; Tim Smith; Perry Tomlin; Lydia Weir-Blankenstein; Michael J. Tipton (European Journal of Applied Physiology, 2013)

Vegetation dynamics across a chronosequence of created wetland sites in Virginia, USA - Douglas A. DeBerry; James E. Perry (Wetlands Ecology and Management, 2012)

Effects of a novel mGlu2/3 receptor agonist prodrug, LY2140023 monohydrate, on central monoamine turnover as determined in human and rat cerebrospinal fluid - Stephen Lowe; Robert Dean; Bradley Ackermann; Kimberley Jackson; Fanni Natanegara; Shelby Anderson; James Eckstein; Eunice Yuen; Mosun Ayan-Oshodi; Mary Ho; David McKinzie; Kenneth Perry; et al. (Psychopharmacology, 2012)

Pacific Rim Forestry - Thomas Brandeis; Olaf Kuegler; Robert Pattison; Örjan Jonsson; James Halperin; Kathleen McGinely; Constance Carpenter; Kathleen Friday; Guy Robertson; Nicklos Dudley; Robert James; Richard Sniezko; et al. (Journal of Forestry, 2011)
68Stakeholders' questions about subtropical and tropical forests can be as diverse and unique as the forests themselves. Obtaining the information needed to begin answering these questions requires innovation and adaptation of existing forest mensuration and inventory techniques that were developed primarily for use in temperate and boreal forests with a strong forest industry presence. Five cycles of forest inventory and monitoring in Puerto Rico and two cycles in the US Virgin Islands under the Forest Inventory and Analysis (FIA) program highlight the commonalities and differences between working in these subtropical forests and the temperate forests of the continental United States. Additionally, the Caribbean implementation of the FIA program has often taken a different approach from that used in the Pacific Islands territories. We can improve on delivery of forest resource information to island stakeholders by studying these experiences. By sharing the lessons learned with other Pacific Rim countries engaging in forest inventory and monitoring, we can learn from each other.

Projected Reorganization of Florida Bay Seagrass Communities in Response to the Increased Freshwater Inflow of Everglades Restoration - Darrell Anthony Herbert; William B. Perry; Bernard J. Cosby; James W. Fourqurean (Estuaries and Coasts, 2011)

Practical neck cooling and time-trial running performance in a hot environment - Christopher James Tyler; Perry Wild; Caroline Sunderland (European Journal of Applied Physiology, 2010)

Pervious and Impervious Urban Stormwater Runoff in a Rapidly Urbanizing Region: Occurrence of Fluoranthene and Pyrene - Rebecca R. James; Perry Wilbon; John P. DiVincenzo (Bulletin of Environmental Contamination and Toxicology, 2010)

Primary Productivity in 20-year Old Created Wetlands in Southwestern Virginia - Robert B. Atkinson; James E. Perry; Gregory B. Noe; W. Lee Daniels; John Cairns (Wetlands, 2010)

Yersinia ironomics: comparison of iron transporters among Yersinia pestis biotypes and its nearest neighbor, Yersinia pseudotuberculosis - Stanislav Forman; James T. Paulley; Jacqueline D. Fetherston; Yi-Qiang Cheng; Robert D. Perry (BioMetals, 2010)

Tree canopy effect on grass and grass/legume mixtures in eastern Nebraska - Michael E. L. Perry; Walter H. Schacht; Gregory A. Ruark; James R. Brandle (Agroforestry Systems, 2009)

Likelihood ridges and multimodality in population growth rate models - Leo Polansky; Perry de Valpine; James O. Lloyd-Smith; Wayne M. Getz (Ecology, 2009)
A central problem in population ecology is to use time series data to estimate the form of density dependence in the per capita growth rate (pgr). This is often accomplished with phenomenological models such as the theta‐Ricker or generalized Beverton‐Holt. Using the theta‐Ricker model as a simple but flexible description of density dependence, we apply theory and simulations to show how multimodality and ridges in the likelihood surface can emerge even in the absence of model misspecification or observation error. The message for model fitting of real data is to consider the likelihood surface in detail, check whether the best‐fit model is located on a likelihood ridge and, if so, evaluate predictive differences of biologically plausible models along the ridge. We present a detailed analysis of a focal data set showing how multimodality and ridges emerge in practice for fits of several parametric models, including a state–space model with explicit accommodation of observation error. Best‐fit models for these data are biologically dubious beyond the range of the data, and likelihood ratio confidence regions include a wide range of more biologically plausible models. We demonstrate the broad relevance of these findings by presenting analyses of 25 additional data sets spanning a wide range of taxa. The results here are relevant to information‐theoretic and Bayesian methods, which also rely on likelihoods. Beyond presentation of best‐fit models and confidence regions around individual parameters, effort toward understanding features of the likelihood surface will help ensure the most robust translation from statistical analysis to biological interpretation.

Parameter estimation in a generalized discrete-time model of density dependence - Leo Polansky; Perry de Valpine; James O. Lloyd-Smith; Wayne M. Getz (Theoretical Ecology, 2008)

High-throughput genotyping with the GoldenGate assay in the complex genome of soybean - David L. Hyten; Qijian Song; Ik-Young Choi; Mun-Sup Yoon; James E. Specht; Lakshmi K. Matukumalli; Randall L. Nelson; Randy C. Shoemaker; Nevin D. Young; Perry B. Cregan (Theoretical and Applied Genetics, 2008)

Virtual observatories for space and solar physics research - Christopher C. Harvey; Michel Gangloff; Todd King; Christopher H. Perry; D. Aaron Roberts; James R. Thieman (Earth Science Informatics, 2008)

Vegetation dynamics in response to organic matter loading rates in a created freshwater wetland in southeastern Virginia - David E. Bailey; James E. Perry; W. Lee Daniels (Wetlands, 2007)

Regression Techniques for Examining Land Use/Cover Change: A Case Study of a Mediterranean Landscape - James D. A. Millington; George L. W. Perry; Raúl Romero-Calcerrada (Ecosystems, 2007)

In vivo pharmacological characterization of the structurally novel, potent, selective mGlu2/3 receptor agonist LY404039 in animal models of psychiatric disorders - Linda M. Rorick-Kehn; Bryan G. Johnson; Karen M. Knitowski; Craig R. Salhoff; Jeffrey M. Witkin; Kenneth W. Perry; Kelly I. Griffey; Joseph P. Tizzano; James A. Monn; David L. McKinzie; Darryle D. Schoepp (Psychopharmacology, 2007)

Abnormal leaf formation in soybean: genetic and environmental effects - James H. Orf; Kevin Chase; James Specht; Ik-Young Choi; Perry B. Cregan; Karl G. Lark (Theoretical and Applied Genetics, 2006)

Vegetation Communities of 20-year-old Created Depressional Wetlands - Robert B. Atkinson; James E. Perry; John Cairns (Wetlands Ecology and Management, 2005)

Postfire Management on Forested Public Lands of the Western United States - ROBERT L. BESCHTA; JONATHAN J. RHODES; J. BOONE KAUFFMAN; ROBERT E. GRESSWELL; G. WAYNE MINSHALL; JAMES R. KARR; DAVID A. PERRY; F. RICHARD HAUER; CHRISTOPHER A. FRISSELL (Conservation Biology, 2004)
Forest ecosystems in the western United States evolved over many millennia in response to disturbances such as wildfires. Land use and management practices have altered these ecosystems, however, including fire regimes in some areas. Forest ecosystems are especially vulnerable to postfire management practices because such practices may influence forest dynamics and aquatic systems for decades to centuries. Thus, there is an increasing need to evaluate the effect of postfire treatments from the perspective of ecosystem recovery. We examined, via the published literature and our collective experience, the ecological effects of some common postfire treatments. Based on this examination, promising postfire restoration measures include retention of large trees, rehabilitation of firelines and roads, and, in some cases, planting of native species. The following practices are generally inconsistent with efforts to restore ecosystem functions after fire: seeding exotic species, livestock grazing, placement of physical structures in and near stream channels, ground‐based postfire logging, removal of large trees, and road construction. Practices that adversely affect soil integrity, persistence or recovery of native species, riparian functions, or water quality generally impede ecological recovery after fire. Although research provides a basis for evaluating the efficacy of postfire treatments, there is a continuing need to increase our understanding of the effects of such treatments within the context of societal and ecological goals for forested public lands of the western United States.

Early Secondary Succession in Bottomland Hardwood Forests of Southeastern Virginia - DAVID R. SPENCER; JAMES E. PERRY; GENE M. SILBERHORN (Environmental Management, 2001)

The effects of 10 days of spaceflight on the shuttle Endeavour on predominantly fast-twitch muscles in the rat - William J. Kraemer; Robert S. Staron; Scott E. Gordon; Jeff S. Volek; L. Perry Koziris; Noel D. Duncan; Bradley C. Nindl; Ana L. Gómez; James O. Marx; Andrew C. Fry; Jerry D. Murray (Histochemistry and Cell Biology, 2000)

Drift and benthic invertebrate responses to stepwise and abrupt increases in non-scouring flow - J. Bosco Imbert; James A. Perry (Hydrobiologia, 2000)

Environmental influences on the availability of smooth pink shrimp, Pandalus jordani , to commercial fishing gear off Vancouver Island, Canada - R. Ian Perry; James A. Boutillier; Michael G.G. Foreman (Fisheries Oceanography, 2000)
Short time scale (less than seasonal) variability in commercial catch rates of smooth pink shrimp, Pandalus jordani, off the west coast of Vancouver Island, Canada, was examined in relation to changes in environmental conditions. Catch per unit of effort (CPUE) data were used as a proxy for catchability to identify environmental conditions affecting the availability of shrimp to the two main gear types in this fishery: otter trawls and beam trawls. Correlogram analyses of the 1996 CPUE (log‐transformed) data from each gear type, and autocorrelation analyses of wind stress, tidal current speed, sea surface temperature and salinity, and hours of bright sunshine (the latter three as residuals from their seasonal trends) for 1996 indicated a mean decorrelation time scale of 7.7 days. This was used to construct smoothed time series of these CPUE and environmental data for 1996. Multiple regression analyses with CPUE as the dependent variable and the environmental data as independent variables were significant, explaining 44% of the variability in otter‐trawl data and 35% of the beam‐trawl variability. Three hypotheses are proposed to explain these results, involving interactions between the shrimp’s behaviour and environmental conditions. A significant proportion of the within‐season variability in CPUE (and therefore in the availability of shrimp to fishing gear) for P. jordani off Vancouver Island can result from variations in environmental conditions which, if included in stock analyses, should reduce the variability of population abundance estimates.

A framework for providing scientific advice for the management of new and developing invertebrate fisheries - R. Ian Perry; Carl J. Walters; James A. Boutillier (Reviews in Fish Biology and Fisheries, 1999)

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)

Temporal changes in the vegetation pattern in a tidal freshwater marsh - James E. Perry; Carl H. Hershner (Wetlands, 1999)

Characterization of the malate dehydrogenase from Thermoleophilum album NM - James F. Novotny; Jerome J. Perry (Archives of Microbiology, 1990)